Industry and Government Perspective in Influenza Control - Slater, Eve E. (2004)
We have had recent reminders of the threats posed by naturally occurring and bioengineered pandemic respiratory infections. It is estimated that if a pandemic infection were to arise anywhere in the world, such an infection would become widespread within 3 months and would have its maximum effect within 6 months. At present, the fastest that a vaccine effective against a new combination of antigens can be developed, purified, and produced is 9–12 months, not counting time for mass production. The current rate at which the production of influenza vaccines can be accelerated is limited by the fact that production is carried out in eggs. Therefore, there is urgent need for cell-based vaccine technologies. These are under way in several centers, yet attainment of a safe product remains several years away. Furthermore, there is need for public and private investment in manufacturing surge capacity and/or dedicated National Institutes of Health facilities to enable accelerated production. We must support efforts to shorten development time by developing and approving subunit antigens and immunogens that anticipate the most virulent viral mutations. Surveillance sites and their electronic interconnections must be expanded. Another component still lacking is funding for laboratories with high throughput screening and strong informatics capabilities to enable the fingerprinting and cataloguing of all known specimens of influenza and other pathogenic organisms for rapid identification of emerging or bioengineered pathogens. In all these efforts, we look to the federal government and to the biomedical research community in both public and private sectors.